Release from Intracellular Stores Is Responsible for Calcium Signaling with von Willebrand Factor in Human Platelets - Kermode, John C.; Milner, Elizabeth P.; Zheng, Qi (Thrombosis and Haemostasis, 2002)
Interaction of von Willebrand factor (VWF) with the platelet promotes hemostasis upon vascular injury. Such interaction raises intracellular free calcium concentration ([Ca2+]i) and induces platelet activation. The platelet [Ca2+]i increase is generally attributed to influx across the plasma membrane. The present study defined the contribution of intracellular calcium stores. Platelet [Ca2+]i was monitored with Fura-PE3. Ristocetin-mediated binding of VWF transiently elevated [Ca2+]i after a lag phase. Studies with 63 healthy donors consistently revealed a VWF-induced platelet [Ca2+]i signal in the absence of extracellular calcium; there was only modest enhancement with extracellular calcium. Blockade of plasma membrane calcium channels did not diminish the signal, whereas depletion or blockade of the intracellular calcium stores abolished it. These findings imply that release from intracellular stores is responsible for the VWF-induced platelet [Ca2+]i increase. Influx across the plasma membrane plays no more than a minor role, probably representing “capacitative entry” to refill the intracellular stores.
Keywords: Glycoprotein Ib-IX-V; intracellular calcium; platelet; signal transduction; von Willebrand factor